2013
DOI: 10.1016/j.cub.2013.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption Leads to Insulin Resistance and Obesity

Abstract: Summary Background Disruption of circadian (daily) timekeeping enhances the risk of metabolic syndrome, obesity, and Type 2 diabetes. While clinical observations have suggested that insulin action is not constant throughout the 24 hour cycle, its magnitude and periodicity have not been assessed. Moreover, when circadian rhythmicity is absent or severely disrupted, it is not known whether insulin action will lock to the peak, nadir or mean of the normal periodicity of insulin action. Results We used hyperins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
278
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(310 citation statements)
references
References 54 publications
12
278
1
6
Order By: Relevance
“…It also regulates daily rhythms of insulin secretion and glucose metabolism, either in a direct or indirect manner. In both humans and rodents, there are robust daily rhythms of glucose tolerance and insulin sensitivity [8,12,13]. Disturbances of the sleep/wake cycle, reduced sleep duration/quality and altered sleep architecture can impair these rhythms, likely contributing to the development of metabolic disease [14][15][16][17][18].…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also regulates daily rhythms of insulin secretion and glucose metabolism, either in a direct or indirect manner. In both humans and rodents, there are robust daily rhythms of glucose tolerance and insulin sensitivity [8,12,13]. Disturbances of the sleep/wake cycle, reduced sleep duration/quality and altered sleep architecture can impair these rhythms, likely contributing to the development of metabolic disease [14][15][16][17][18].…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
“…Without question, poor diet, lack of exercise, obesity and chronic insulin resistance are major contributing factors. One basic function that appears to be heavily influenced by (and also influences) obesity and metabolic disease is the internal timing system [6][7][8][9][10]. The timing system drives daily rhythms of physiology and behaviour, including the alternating pattern of feeding and fasting [11].…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
“…Likewise other physiological functions, glucose metabolism is regulated by circadian system (43,44). In an experiment, study Clock mutant mice showed lack of rhythmicity in the action of insulin, a condition which was reversible once the clock protein was reintroduced (43). The removal of pancreatic Clock and Bmal1 in mice resulted in functional defects in insulin secretion and decreases in islet size and survival, signifies a key role of peripheral clocks in the regulation of glucose homeostasis (45).…”
Section: Melatonin and Circadian Rhythmmentioning
confidence: 99%
“…Likewise other physiological functions, glucose metabolism is regulated by circadian system (43,44). In an experiment, study Clock mutant mice showed lack of rhythmicity in the action of insulin, a condition which was reversible once the clock protein was reintroduced (43).…”
Section: Melatonin and Circadian Rhythmmentioning
confidence: 99%
“…A causal role for a disturbed circadian rhythm in the development of obesity has been demonstrated by animal studies. Mice with genetically dysfunctional clock genes develop obesity and insulin resistance (6)(7)(8)(9). Moreover, specific ablation of the SCN induces acute weight gain (10).…”
mentioning
confidence: 99%